Karakterisasi Senyawa Isoprenoid dan Pertumbuhan Semai Mangrove Avicennia alba Bl. - Mulyar Hamka; Mohammad Basyuni; Lollie Agustina (Program studi Kehutanan USU, 2012)
This study aims to determine the characterization of isoprenoid compounds in the mangrove A. alba and seedling growth of A. alba at different levels of salinity. The results showed the total lipids in the leaves of A. alba (21 mg) was higher than that in the roots (11,7 mg). Total Non Saponifiable Lipids (NSL) content in the leaves of A. alba (1,1 mg) greater than that in the roots (0,6 mg). NSL composition of A. alba consists of 3 major factions namely triterpenoids, phytosterols, and other compounds. Phytosterol composition in the leaves and roots of A. alba showed the presence of compounds such as campesterol, stigmasterol and β-sitosterol. As frase for the composition triterpenoid found the presence of β-amyrin, germanicol, betulin, lupeol and α-amyrin. Phytol, cholesterol, and squalene were also found as the other compounds. The content of the NSL triterpenoid was higher than phytosterol in the leaves and roots of A. alba. The results also showed that phytol compounds had the highest content of leaves of A. alba (71.4 %) and the β-sitosterol had the highest content of root A. alba (27.8 %). Based on the analysis of the effect of salinity on seedling growth of A. alba showed that the salinity of 2% significantly affected the seedling height and diameter of 3 months of A. alba. Keywords :Avicennia alba, Non Saponifiable Lipids (NSL), Triterpenoid, Phytosterol, and Salinity.